Era Digitalisasi: Membawa Kesenjangan, Ide Sulit Berkembang? - Junaedi, Nurasikin; Asbari, Masduki; Naja, Rif'atun; Jodyapati, Satrio (AGUSPATI RESEARCH INSTITUTA, 2024)
The purpose of this study is to find out something that can eliminate a group in the era of Digitalization. In this study report, using descriptive qualitative methods by taking notes, because the source of the data obtained by listening to oral narration from the Gita Wirjana youtube channel entitled